(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The language of the press has a speech structure, which is manifested in the special selection of language tools and their activity. This article talks about the language features of Arabic newspaper texts in Arab countries and the problems of their translation into another language.